1999
DOI: 10.1007/s004670050555
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of focal segmental glomerulosclerosis in nephrotic syndrome of childhood

Abstract: In recent adult literature, there have been reports of an increasing incidence of focal segmental glomerulosclerosis (FSGS) among patients with nephrotic syndrome. To examine whether this observation is also relevant to the pediatric population we utilized our hospital computerized database to analyze the data on children with primary nephrotic syndrome seen first between the years 1984 and 1995. A questionnaire was also sent to all metropolitan Kansas City pediatricians to identify possible patients outside t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
126
6
11

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(150 citation statements)
references
References 13 publications
7
126
6
11
Order By: Relevance
“…This variation might be related to differences in ethnic composition, biopsy indication policies, or periods of observation analyzed. A trend toward an increasing incidence of FSGS has been noted in several studies (9)(10)(11). The other, much rarer histopathologic entities DMS, membranoproliferative GN, and membranous nephropathy typically presented with milder hypoalbuminemia and a slightly higher prevalence of hypertension than MCN, MesPGN, and FSGS.…”
Section: Discussionmentioning
confidence: 86%
“…This variation might be related to differences in ethnic composition, biopsy indication policies, or periods of observation analyzed. A trend toward an increasing incidence of FSGS has been noted in several studies (9)(10)(11). The other, much rarer histopathologic entities DMS, membranoproliferative GN, and membranous nephropathy typically presented with milder hypoalbuminemia and a slightly higher prevalence of hypertension than MCN, MesPGN, and FSGS.…”
Section: Discussionmentioning
confidence: 86%
“…Pediatric FSGS is a disease of increasing incidence and represents a major cause of chronic kidney disease (CKD) (6,7,15,16). One recent study in pediatric FSGS showed that there was no difference in renal survival on the basis of histologic variants, although the outcome of the patients in the study was significantly more favorable than in previous studies.…”
mentioning
confidence: 79%
“…Only 68.9% of these patients underwent renal biopsy; those without biopsy were assumed to have minimal change disease. 19 It has been suggested that renal biopsy findings in recent published series are not representative of the true incidence of the various histopathological categories, as in many centres renal biopsy is only recommended for patients who do not respond to steroids. 13 The distribution of the histological subtypes is related to gender, age and ethnicity of the population.…”
Section: Epidemiologymentioning
confidence: 99%